Evaluation of myopia status and eye use behavior in school-age and preschool children - Xiaolian Xie; Juan Ma; Qi Chen; Xiuna Li; Leina Jia; Juan Cao (PLoS ONE, 2025)
Background The aim of this research was to assess the incidence of myopia and associated behavioral risk factors among school-aged and preschool children in Ningxia. Methods Our survey conducted a comprehensive cross-sectional study utilizing questionnaires to investigate the risk factors for myopia in children aged 3–10, both in preschool and school-age, based on parental reports of their children’s myopia status. The logistic regression model analysis was performed using myopia as dependent variables. Results In Ningxia, the prevalence of myopia among preschool and school-age children stood at 4.9%. Specifically, the rate for school-age children (6.3%) was notably higher than that for preschool children (3.7%), with the difference being statistically significant (P < 0.05). The results of the logistic regression analysis indicated that senior grade, parental myopia, academic stress, playing electronic products, reading e-books for a long time, eye fatigue and less outdoor activities were risk factors for myopia, while not staying up late and reasonable reading distance (33–35 cm) were protective factors for myopia. Conclusions The incidence of myopia among children aged 3–10 in Ningxia is 4.9%. Additionally, a child’s likelihood of developing myopia is influenced by whether their parents have myopia. Reading e-books and long-term exposure to electronic products are associated with myopia; Eye fatigue and academic stress are also important factors affecting myopia.